AKTIVITAS ANTITUBERKULOSIS EKSTRAK KULTUR CAIR Streptomyces ENDOFIT RIMPANG Kaempferia galanga TERHADAP Mycobacterium tuberculosis RESISTEN - Siti Nur Azizah, Mikhania Cristiningtyas Eryani (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2019)
The objective of this research was to examine the antituberculosis activity of drug resistant stains using liquid culture extracts Streptomyces Kaempferia galanga rhizomes. The endophytes Streptomyces, there were KJ.3A, KJ3B, KJ.4, and KJ.11. Two resistant strain of Mycocacterium tuberculosis were used, there were HE strain which resistant to isoniazid dan etambutol and SR stainswhich resistant to streptomisin and rifampisin. The liquid culture extracts of Streptomyces endophytes was obtained from centrifugation method by growing Streptomyces colony into YMB media Antituberculosis activity was using Lowen-stein Jensen (LJ) methode after incubation for 8 weeks. The result showed that the four liquid culture extracts Streptomyces endophytes have not been able to inhibit the growth of Mycobacterium tuberculosis in both HE and SR strainsKeywods: Antituberculosis, endofit Streptomyces, resistant M. tuberculosis